Cross cultural research: experiences in sundanese wayang golek of West Java (Móin-Móin Magazine - Studies in the Art of Puppetry, 2018)
Studying the performing art of wayang golek in the late 1970s requiredlearning how to learn a complex art in a local language from village practitionerswhose practice did not correspond to the model expounded by the local academic.Language, music, culture, dance, spiritual dimensions, and complex stories neededto be absorbed and became building blocks toward performing this rich art of theSundanese dalang of West Java.Keywords: Wayang Golek. Sundanese rod puppetry. Dalang.